Improving employee performance through Streng thening training and education levels - Susi Handayani; Yulianingsih Yulianingsih; Yopi Okta Sali (Enrichment : Journal of Management, 2023)
Susi Handayani, et al conducted a study entitled Improving Employee Performance Through Strengthening Training and Education Levels (Study at Hotel Mauve Palembang), using a sample of 43 employees of Mauve Hotel Palembang. The results showed that the training variable had a significant effect on employee performance with a tcount value of the training variable (X₂) of 2.040 > ttable 2.021, a significance value of 0.048 <0.05. Furthermore, simultaneously the level of education and training has a significant effect on employee performance with Fcount 36.678 > Ftable 3.23, the significance is less than 0.05 (0.036 <0.05). The better the level of education applied to Mauve Hotel Palembang employees, the higher the employee performance, this is shown from the coefficient that is owned by variable X1 which is positive.